Diarrhea outpatient and inpatient utilization and cost accumulation among children under five by birth weight category in Indonesia: an analysis of BPJS Kesehatan sample data - Rahmawati, Latifah Alifiana; Nurwahyuni, Atik (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to determine the number of outpatient and inpatient diarrhea cases, the duration of hospital stays, and the accumulated cost of claims paid to health facilities for diarrhea treatment by birth weight category among children under five. We collected this data from the referral health facility (FKRTL) using the Indonesian Social Security Agency for Health (BPJS Kesehatan) Sample Data from 2017-2022. Methods: This retrospective cohort design uses BPJS Health Sample Data from 2017-2022, merged with the Water Quality Index from the Ministry of Environment and Forestry Report. Using negative binomial regression, we calculated the rate ratio of the number of outpatient and inpatient cases and the duration of hospital stays. We estimated the cost accumulation using Gamma Regression. Results: The subjects of this study were 3,175 children born in 2017. Among these, 493 (15.53%) were low birth weight children. The average number of outpatient and inpatient diarrhea visits, the duration of hospital length of stay, and the accumulated costs of diarrhea treatment were higher in low birth-weight children than in normal birth-weight children. A strong association existed between low birth weight, the number of outpatient cases, and the length of hospital stays. Conclusion: Birth weight, gender, membership segment, treatment class, area of ​​residence, and water quality index significantly influenced the number of outpatient visits for children aged 0 to 5 years at FKRTL caused by diarrhea.